Renal dysplasi hos hund - Berg, Nina (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2012)
Renal dysplasia in dogs is a severe kidney disease that causes great suffering for the affected individual. The disease disturbs the development of the kidneys which leads to an immature microscopic structure of the kidney and smaller kidneys than normal. A dog with renal dysplasia only lives between 4 and 24 months, because of kidney failure. There are different ways to establish a diagnosis, but the most common way today is to take a renal biopsy. In a scientific study, ultrasound based diagnosis was shown to match the histopathological picture of the disease. Looking ahead, one can imagine that a diagnosis based on ultrasound is possible. Renal dysplasia is a heritable disease with an unknown inheritance pattern. Research about the genetic background is ongoing, potentially resulting in a DNA-test. DOGenes in Canada already offers an online test for renal dysplasia in 38 breeds. The Swedish Kennel Club (SKK) has central registration for renal dysplasia in twelve breeds. This implies that the result from analysis of the biopsy in case of renal dysplasia is made publicly available at the SKK website. SKK’s recommendations are that affected dogs, their offspring and parents should not be used in breeding. Already in 1974 renal dysplasia was diagnosed in Sweden, which indicates that the condition has existed for some time. During the literature study it became clear that the disease is spread around the world, based on the published research that was found from for instance Australia, Italy and Japan. Because the disease is so severe and causes great suffering for the affected dog, better routines for recording of renal dysplasia and more research is required in the future. SAMMANFATTNING Renal dysplasi hos hund är en allvarlig njursjukdom som orsakar lidande hos den drabbade individen. Njurarna utvecklas inte helt normalt vilket orsakar en omogen mikroskopisk struktur i njuren och makroskopiskt mindre njurar än det normala. Sjukdomen leder till njursvikt och livslängden för en sjuk hund ligger mellan 4 till 24 månader. Det finns olika sätt att få en diagnos ställd, det vanligaste sättet idag är att ta en njurbiopsi. Diagnos baserad på ultraljud har i en studie visat sig stämma bra överens med den histopatologiska bilden av sjukdomsgraden. Framöver kan man alltså tänka sig att en diagnos enbart baserad på ultraljud inte är omöjlig. Renal dysplasi är en ärftlig sjukdom med ett ännu oklart nedärvningsmönster och forskning för att få fram gentest pågår. DOGenes i Kanada erbjuder redan idag via internet ett DNA-test för renal dysplasi för 38 raser. Svenska kennelklubben (SKK) har central registrering för renal dysplasi hos tolv raser. Detta innebär att analysen av biopsin som tas hos dessa raser redovisas offentligt hos SKK i det fall resultatet pekar på renal dysplasi. De hundar som visar sig vara sjuka rekommenderar SKK att man tar ur aveln, likaså deras föräldrar och avkomma om sådan redan finns. Redan 1974 diagnosticerades hundar i Sverige med renal dysplasi, detta tyder på att problem med sjukdomen funnits en längre tid. Att sjukdomen finns utspridd över världen har framkommit under denna litteraturstudie då forskning gjorts i bland annat Australien, Italien och Japan. Eftersom sjukdomen är så pass allvarlig och orsakar stort lidande hos den drabbade hunden krävs bättre rutiner avseende registrering av data och mer forskning kring renal dysplasi för att underlätta bekämpningen av sjukdomen.